On the impossibility of core-selecting auctions - Jacob K. Goeree; Yuanchuan Lien (Theoretical Economics, 2016)
When goods are substitutes, the Vickrey outcome is in the core and yields competitive seller revenue. In contrast, with complements, the Vickrey outcome is efficient but not necessarily in the core and revenue can be low. Non-core outcomes may be perceived as unfair since there are bidders willing to pay more than the winners' payments. Moreover, non-core outcomes render the auction vulnerable to defections as the seller can attract better offers afterwards. To avoid instabilities of this type, Day and Raghavan (2007), Day and Milgrom (2008), and Day and Cramton (2012) have suggested adapting the Vickrey pricing rule so that outcomes are in the core with respect to bidders' reported values. If truthful bidding were an equilibrium of the resulting auction then the outcome would also be in the core with respect to bidders' true values. We show, however, that when the equilibrium outcome of any auction is in the core, it is equivalent to the Vickrey outcome. In other words, if the Vickrey outcome is not in the core, no core-selecting auction exists. Our results further imply that the competitive equilibrium outcome, which always exists when goods are substitutes, can only be implemented when it coincides with the Vickrey outcome. Finally, for a simple environment we show that compared to Vickrey prices the adapted pricing rule yields lower expected efficiency and revenue as well as outcomes that are on average further from the core.
Keywords: D44; 330; Core outcomes; Vickrey auction; substitutes; complements; competitive equilibrium; Bayesian implementability